RIGID BODY HOME EXPERIMENT IN A PHYSICS COURSE AT A TECHNICAL UNIVERSITY - Podlasov, Serhii; Dolianovska, Olha; Matviichuk, Oleksii (Physical and Mathematical Education, 2024)
The methodology of conducting a home natural experiment to study the plane motion of a rigid body using the example of a homemade analog of Maxwell's pendulum is considered.Formulation of the problem. Physics is an experimental science; therefore, student engagement in experimental research is integral to its teaching methodology. During the execution of experiments, students verify the consequences of the laws of physics and acquire practical experimental skills. Students can only conduct natural experiments at home using readily available equipment in distance learning. An example of such research is the study of the motion of a homemade analog of Maxwell's pendulum. Its execution allows students to gain a better understanding of theoretical concepts, develop skills in preparing and conducting natural experiments, and analyze the obtained results.Materials and methods. The study is based on the analysis of the curriculum of the physics course for undergraduate students of a technical university, a review of the literature on the research topic, experiments on the dynamics of the plane motion of a rigid body, and tasks of the physics course on this topic—also, methods and means of measuring short-term mechanical motion at home.Results. A Yo-Yo toy or its homemade analog can be used as a Maxwell's pendulum. The paper demonstrates the design of pendulums that NTUU "KPI" students created to conduct the research. The obtained data enable students to experimentally confirm the laws of rigid body dynamics.Conclusions. Creating Maxwell's pendulum analog and conducting an experiment with its help allows students to acquire specific experimental skills and learn to work out the results of a natural experiment using the laws of rigid body dynamics. The constructed device can be used for laboratory research at home and as a basis for experimental tasks. According to the students, conducting experiments at home is exciting and helpful in improving their understanding of the concepts of rigid body dynamics.
Keywords: home experiment; Maxwell's pendulum; analysis of the experiment